Epidemiology of illness during the super 14 rugby tournament – a prospective cohort study. Issue 4 (27th March 2011) - Schwellnus, M; Derman, W; Lambert, M; Redhead, C; Page, T
Abstract : Background: There is some evidence suggesting that medical illness can account for a significant proportion of consultations by a team physician travelling with a group of elite athletes. The Super 14 Rugby tournament is conducted over a 3 months period and involves intercontinental travel. Objective: The purpose of this study was to determine the incidence of medical illness in rugby players participating in the 2010 Super 14 Rugby tournament. Setting: 2010 Super 14 Rugby tournament. Participants: A cohort of elite rugby players from eight Super 14 rugby teams (average squad size of 30 players) was recruited. Assessment: All players completed a pre-competition questionnaire pertaining to personal details, training history, personal general medical history and medication. Players were then followed daily over the 3 month competition period (total of 20 836 player days). Team physicians completed a daily medical illness and treatment log using a newly developed illness coding system based on the ICD10 codes (100% compliance). Information included the daily squad size and illness details (system affected, final diagnosis, symptoms, treatment and training/match days lost). Main outcome measurement: Incidence of illness (illness per 1000 player days). Results: The overall incidence of illness in the cohort was 21.4 per 1000 player days. The highest incidence (per 1000 player days) of illness by system was in the respiratory system (6.6), gastro-intestinal system (5.9) and the dermatological system (4.7). Respiratory tract illness accounted for 31% of all illness followed by the gastro-intestinal system (28%) and the dermatological system (22%). Conclusion: Medical illness is common in elite rugby players participating in an international tournament over a 3-month period. Respiratory tract, gastro-intestinal tract and dermatological illness accounted for over 80% of these illnesses.